Stereotactic Body Radiation Therapy vs. Transarterial Chemoembolization in Inoperable Barcelona Clinic Liver Cancer Stage a Hepatocellular Carcinoma: A Retrospective, Propensity-Matched Analysis - Su, Ting-Shi; Liang, Ping; Zhou, Ying; Huang, Yong; Cheng, Tao; Qu, Song; Chen, Long; Xiang, Bang-De; Zhao, Chang; Huang, De-Jia; Liang, Shi-Xiong; Li, Le-Qun (Frontiers in Oncology, 2020)
Background and Objective: It is unclear if stereotactic body radiation therapy (SBRT) or transarterial chemoembolization (TACE) is better for the treatment of inoperable early-stage hepatocellular carcinoma (HCC). This study aimed to retrospectively compare the efficacy of SBRT to TACE in patients with inoperable Barcelona Clinic Liver Cancer (BCLC)-A stage HCC. Materials and Methods: In this multi-institutional retrospective study, a total of 326 patients with inoperable BCLC-A stage HCC were enrolled. Totally, 167 patients initially received SBRT and 159 initially received TACE. Overall survival (OS), local control (LC), intrahepatic control (IC), and progression-free survival (PFS) were evaluated in univariable and propensity-score matched analyses. Results: There was a smaller median tumor size in the SBRT group than in the TACE group (3.4 cm versus 7.2 cm, P<.001). After propensity score matching in the selection of 95 patient pairs, SBRT had better LC, IC, and PFS than TACE but showed comparable OS. The accumulative 1-, 3-, and 5-year OS rates were 85.7%, 65.1%, and 62.8% in the SBRT group and 83.6%, 61.0%, and 50.4% in the TACE group, respectively (P=.29). The accumulative 1-, 3-, and 5-year PFS were 63.4%, 35.9%, and 27.5% in the SBRT group and 53.5%, 27.4%, and 14.2% in the TACE group, respectively (P=.049). The accumulative 1-, 3-, and 5-year LC were 86.8%, 62.5%, and 56.9% in the SBRT group and 69.3%, 53.3%, and 36.6% in the TACE group, respectively (P=.0047). The accumulative 1-, 3-, and 5-year IC were 77.3%, 45.9%, and 42.4% in the SBRT group and 57.3%, 34.1%, and 17.7% in the TACE group, respectively (P=.003). On multivariate analysis, treatment (SBRT versus TACE) were significant covariate associated with local and intrahepatic control (HR=1.59; 95% CI: 1.03-2.47; P=.04; HR=1.61; 95% CI: 1.13-2.29; P=.009). Conclusions: SBRT was an alternative to TACE for inoperable BCLC-A stage HCC with better local and intrahepatic control. Controlled clinical trials are recommended to evaluate the actual effects of this novel regimen adequately.